A Vibrant European Labor Market with Full Employment - Jo Ritzen; Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 2013)
We sketch a visionary strategy for Europe in which full employment is quickly regained by 2020, where income inequality is reduced and the economies are more sustainable. We name this scenario vibrant. It is contrasted with what would happen if present policies continue within the European Union (EU) and its member states. In the vibrant scenario, full employment is regained by more policy attention toward innovation and its underlying research and development (R&D), accompanied by more labor mobility within and between EU countries, in combination with a selective immigration policy based on labor market shortages. The road to full employment is embedded in a landscape with less income inequality and more greening of EU member states' economies. We translate the vibrant scenario into policy proposals distinguishing between the role for the EU and that of the member states. We hope these proposals will be included in the election programs for the upcoming 2014 European Parliament elections and in developing the mandate for the new European Commission in December 2014.
Keywords: D31; D33; F55; I23; I24; I25; I28; J11; J18; J21; J31; J64; J83; O31; O38; O52; 330; employment; labor mobility; innovation; income inequality; competition; labor markets; greening; happiness